Prediction of radiotherapy effect based on evaluation of radiosensitivity of normal and cancer tissue – limitations and possibilities - Szyfter, Krzysztof; Milecki, Piotr (Contemporary Oncology/Współczesna Onkologia, 2003)
Radiotherapy plays an important role in the treatment of many cancers. Unfortunately, the patient’s survival and the intensity of radiation complications are still far from the expected results. For this reason predicting the response of irradiated tumours and intensity of side effects would be very useful in the process of qualifying patients for radiotherapy. Adequately sensitive and specific tests of radiosensitivity would allow for the individualization of treatment. A variety of DNA damage assays have been applied in an effort to predict the sensitivity of cells to ionizing radiation. Currently, a few predictive tests are still under clinical evaluation. The colony-forming test after applied test dose of 2Gy (SF2) is one of them. However, mainly due to relatively long waiting time needed for results, the test is not applied in the routine practice. Analysis of chromosome damage can be a useful method in the evaluation of radiotherapy effects. Among tests from this group, comet assay and micronuclei tests (MN) should be mentioned above all. Molecular analysis of genes involved in response to radiotherapy is another type of research field enabling the prediction of radiotherapy effects. This research is very promising but currently it is at the initial phase of evaluation. In summary, an attempt to do research on possibility of the prediction of tumour response to radiotherapy effects is very tempting. However, currently none of tests can be routinely applied. It seems that the greatest chance for application will have a test which is fast and cheap and above all which strongly correlates with the results of radiotherapy.